2013
DOI: 10.1111/myc.12115
|View full text |Cite
|
Sign up to set email alerts
|

MALDI‐TOF mass spectrometry identification of filamentous fungi in the clinical laboratory

Abstract: This study aimed to validate the effectiveness of a standardised procedure for the MALDI-TOF mass spectrometry (MS)-based identification on a large sample of filamentous fungi routinely identified in university hospitals' laboratories. Non-dermatophyte filamentous fungi prospectively isolated in the routine activity of five teaching hospitals in France were first identified by conventional methods in each laboratory and then by MS in one centre. DNA sequence-based identification resolved discrepancies between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
71
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 23 publications
4
71
0
8
Order By: Relevance
“…The majority of published studies examining large study sets of filamentous fungi utilize the Bruker Biotyper MALDI-TOF MS and the associated library and/or laboratory-developed libraries (10,11,(15)(16)(17)(18). Prior studies have evaluated the accuracy of MALDI-TOF MS for the identification of only a few genera or groups of organisms, such as Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published studies examining large study sets of filamentous fungi utilize the Bruker Biotyper MALDI-TOF MS and the associated library and/or laboratory-developed libraries (10,11,(15)(16)(17)(18). Prior studies have evaluated the accuracy of MALDI-TOF MS for the identification of only a few genera or groups of organisms, such as Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the MALDI-TOF MS approach was also applied to mold identification and was shown to be able to accurately identify a wide array of species from various genera or groups of clinical interest, including Aspergillus spp. and dermatophytes (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Species identification by MALDI-TOF MS within the Fusarium genus has not yet been thoroughly investigated.…”
mentioning
confidence: 99%
“…Compared to that of bacteria, the cell wall of molds is more robust and rigid, making sample preparation more labor-and time-intensive (13,14). Several studies reported the generation of in-house databases for the Bruker MALDI Biotyper (Bruker Daltonik, Bremen, Germany) covering mainly single genera, such as Aspergillus (15), Fusarium (15, 16), Lichtheimia (17), or the Pseudallescheria/Scedosporium complex (18); orders, such as the Mucorales (15); and individual groups of fungi, such as the dermatophytes (19,20) or clinically important molds (14,(21)(22)(23). However, the species coverage of most of these fungus databases is limited, and many are neither publicly nor commercially available.…”
mentioning
confidence: 99%